Violence and gender in the globalized world (London ; New York)
1 online resource (xix, 296 pages)
Keywords: Violence and Gender in the Globalized World expands the critical picture of gender and violence in the age of globalization by introducing a variety of uncommonly discussed geo-political sites and dynamics. The volume hosts methodologically and disciplinarily diverse contributions from around the world, discussing various contexts including Chechnya, Germany, Iraq, Kenya, Malaysia, Nicaragua, Palestine, the former Yugoslavia, Syria, South Africa, the United States, and the Internet. Bringing together scholars' and activists' historicized and site-specific perspectives, this book bridges the g.